2022
DOI: 10.1038/s41598-022-06820-5
|View full text |Cite
|
Sign up to set email alerts
|

Origin of observed narrow bandgap of mica nanosheets

Abstract: Mica nanosheets possess peculiar feature of narrowed bandgap with the decrease of thickness but a conclusive theoretical understanding of the narrowing mechanisms is still under development. In this report, first-principles calculations were carried out to investigate the electronic band structure of mica nanosheets with the deposition of K2CO3. Bulk mica shows an indirect bandgap of 4.90 eV. Mica nanosheets show similar electronic structures to bulk mica with a gradually increased bandgap of 4.44 eV, 4.52 eV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…The formation of K 2 CO 3 on the mica surface has been previously reported in experiments, 33 and further insights have been gained through first-principles calculations conducted by our research group. 34 Our study demonstrated that the calculated binding energy between few-layered mica and K 2 CO 3 is negative, indicating a favorable interaction. Additionally, we found that K 2 CO 3 had a greater affinity for mica nanosheets than for bulk mica.…”
Section: Electrical Resistance Of Exfoliated Micamentioning
confidence: 58%
See 1 more Smart Citation
“…The formation of K 2 CO 3 on the mica surface has been previously reported in experiments, 33 and further insights have been gained through first-principles calculations conducted by our research group. 34 Our study demonstrated that the calculated binding energy between few-layered mica and K 2 CO 3 is negative, indicating a favorable interaction. Additionally, we found that K 2 CO 3 had a greater affinity for mica nanosheets than for bulk mica.…”
Section: Electrical Resistance Of Exfoliated Micamentioning
confidence: 58%
“…Additionally, we found that K 2 CO 3 had a greater affinity for mica nanosheets than for bulk mica. 34 This K 2 CO 3 layer enhances electron transfer to CO 2 and facilitates further CO 2 adsorption through physisorption. 7 Moreover, the efficiency of many CO 2 capture systems can be affected by contaminants like water vapor or other organic substances.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is known that preparing mica surfaces that are truly clean is not easy, since mica has a high-energy surface that readily adsorbs water, organic contaminants, and gases from the atmosphere. Previous experimental and theoretical studies suggest the deposition of potassium carbonate (K 2 CO 3 ) crystals on the mica surface, [ 27 , 51 , 52 , 53 ] which can be attributed to the reaction of ambient water and CO 2 with surface K + ions. Considering that our eMica nanosheets are prepared and maintained in an open environment rather than under an ultrahigh vacuum, it is relatively impossible to avoid deposition of K 2 CO 3 on the high-energy mica monolayer surface, which is in agreement with the presence of C=O in XPS analysis of eMica nanosheets ( Figure 6 c).…”
Section: Results Discussionmentioning
confidence: 99%
“…The stable supercell structure of mica, mica monolayer and K 2 CO 3 -deposited mica monolayer obtained in our previous work [ 27 ] was adopted to investigate their CO 2 adsorption behavior. Mica surface was obtained by cleaving the bulk in the (001) direction.…”
Section: Methodsmentioning
confidence: 99%
“…39 Mica consists of two tetrahedral (aluminium, silicon, oxygen) units and an octahedral unit (aluminium, oxygen, hydrogen), and an interlayer cation (potassium). 40 The presence of hydroxyl and oxygen groups on the surface of MNS could facilitates its interaction with PVDF chains, enhancing the β-phase content of the latter. Also, MNS could enhance the dielectric properties of PVDF.…”
Section: Introductionmentioning
confidence: 99%